Experimental study on the evolution of mechanical properties of hot dry rocks under alternating temperature loads. (January 2023) - Wang, Daobing; Dong, Yongcun; Wang, Qiuyan; Sun, Dongliang; Yu, Bo
Highlights: A new idea is proposed to improve the fracability of hot dry rock under alternating temperature loads. Effects of alternating temperature loads on mechanical properties of hot dry rock are experimentally investigated. Microstructure analysis under alternating temperature loads are given in detail. Abstract: Inspired by the physical process of thermal expansion and cold shrinkage, this study proposes a new idea to improve the capacity to form complex fractures (i.e., fracability) in hot dry rock (HDR) under alternating temperature loads. However, the evolution of the HDR mechanical properties under alternating temperature loads is rarely reported. This study analyzed the evolution mechanism of the HDR rock mechanics properties under alternating temperature loads by using the high-temperature high-pressure rock mechanics triaxial test system. The results show that mechanical parameters such as compressive strength, dilatancy stress, and elastic modulus are significantly reduced after alternating temperature loading, compared with those after simple heat treatment. After alternating temperature loading, compared with the case of simple heat treatment, the HDR rock samples reach the dilatancy stress earlier; its stress-strain curve features a visible concave arc at the micro-fracture closure segment; the axial loading ends up with the shear failure and enhanced complexity. The microstructural analysis shows that cyclic thermal stress occurs inside the HDR as the temperature increases and extensive mineral metasomatism is triggered, which is dominated by quartz penetrating plagioclase via metasomatism. Therefore, the decrease of quartz content and the HDR mineral metasomatism under alternating temperature loads are the fundamental causes for the great changes in the HDR mechanical properties.